2015
DOI: 10.3823/754
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistant bacteria in terrestrial and aquatic environments: A review

Abstract: Antibiotic resistant bacteria have become increasingly widespread in the environment and their prevalence is a serious potential problem for human health. The rise and spread of this resistance is primarily due to the overuse of antibiotics in clinical therapeutics and as growth promoters for livestock. Overuse undermines the usefulness of antibiotics by giving a selective advantage to microbes that are resistant. The problem has been exacerbated by the emergence of bacteria that are resistant to multiple anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…They reported that most isolates were multi-drug resistant against amoxicillin, cloxacillin, cefotaxime, and penicillin. Al-Bahry et al (2014) determined that wastewater from hospitals, pharmaceutical factories, and agricultural runoff contaminates surface and groundwater by introducing various antibiotic-resistant bacteria (MARB) and antimicrobial medicines.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that most isolates were multi-drug resistant against amoxicillin, cloxacillin, cefotaxime, and penicillin. Al-Bahry et al (2014) determined that wastewater from hospitals, pharmaceutical factories, and agricultural runoff contaminates surface and groundwater by introducing various antibiotic-resistant bacteria (MARB) and antimicrobial medicines.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial agents, even at sub-inhibitory levels in aquatic environments, can stimulate the expression of resistance genes, thereby promoting antimicrobial resistance (Cornejova et al, 2015;WHO, 2014). Frequent exposure to antibiotics is the primary driver behind the emergence of antibiotic-resistant bacteria in wastewater systems (Al-Bahry et al, 2014). Several classes of antibiotics have been frequently detected in sewage, activated sludge, digested sludge, and e uents, posing a risk of antibiotic resistance (Watkinson & Costanzo, 2017;Zhang & Li, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a natural phenomenon, antibiotic resistance is a condition where bacteria become less susceptible to the antibiotic to which it was once vulnerable. The development of antibiotic resistance is driven by complex evolutionary processes that influence the selection pressure by the application of antibiotics [3,4,5]. The emergence of new infectious diseases and the resurgence of many infections that have been treated necessitates the use of antibiotics, which has substantially contributed to the recent surge of resistant bacterial pathogens of public and clinical importance [6].…”
Section: Introductionmentioning
confidence: 99%